USE OF REMOTE SENSING TECHNIQUE IN THE LANDUSE/LANDCOVER EVALUATION OF DRY RAIN FOREST OF SOUTHWESTERN NIGERIA (2012)
The dearth of up-to-date information on the Nigerian natural resources is a major hindrance to their optimal and sustainable use for national development. Remote sensing technique enables faster and more accurate acquisition of information than that of conventional approach to natural resources survey. However, their uses are yet to be fully exploited. This study was therefore designed to produce LandUse/LandCover (LULC) maps of Southwestern Nigeria using remote sensing technique and also evaluate soils of the same area for crop production. Multidate maps (1975, 1986 and 2002 of LULC covering 23,629.2 ha for Ife and 13,653 ha for Ilesha areas were derived from aerial photographs of 1975 using mirror stereoscopes and Landsat thematic mapper data for 1986 and 2002. The changes in the LULC were evaluated for built-up, hill/water, fallow/cropland and forest areas. Semi-detailed soil maps of the two areas were produced using aerial photographs and Systeme Probatoire Pour Observation de la Terre (SPOT) Imagery to evaluate the degree of concordance between them. The soil series identified using FAO guidelines were evaluated for potential crop suitability using Land Evaluation Computer (LEC) system. Data were analyzed using descriptive statistics. In LULC of Ife area, there was a general increase of 4.2% (1975 – 1986) and 5.6% (1986 – 2002) in built-up areas; 1.4% (1975 – 1986) and 4.2% (1986 – 2002) in the fallow/crop areas; 0.88% (1975 – 1986) and 3.7% (1986 – 2002) in Hill/Water areas; and a decrease of 3.7% (1975 – 1986) and 5.0% (1986 – 2002) in the forest areas. Concordance between the two soil maps of the area was 32.0%. Thirteen soil series were identified out of which four (Araromi, Itagunmodi, Owena and Egbeda) series were moderately suitable (S2) for maize; seven were moderately suitable (S2) for upland rice (Iregun, Araromi, Itagunmodi, Owena, Olorunda, Oba and Egbeda); eight were moderately suitable (S2) for yam (Okemessi, Erin-Oke, Etionni, Iregun, Araromi, Itagunmodi, Owena and Egbeda) and for cassava five (Iregun, Araromi, Itagunmodi, Owena and Egbeda) were moderately suitable (S2). Similarly in Ilesha area, there was a general increase of 4.0% (1975 – 1986) and 0.3% (1986 – 2002) in the built-up areas; 2.3% (1975 – 1986) and 8.8% (1986 – 2002) in the fallow/crop land areas, 2.1% (1975 – 1986) and 2.6% (1986 – 2002) for Hill/Water areas; and a decrease of 8.4% (1975 – 1986) and 6.5% (1986 – 2002) for forest areas. Concordance between the two soil maps of the area was 54.9%. Fourteen soil series were identified out of which ten were of the same suitability class as those of Ife area. Of the remaining four series (Omo, Jago, Ondo and Irapa), two (Ondo and Jago) were marginally UNIVERSITY OF IBADAN LIBRARY iii suitable (S3) for maize and upland rice. Ondo series was moderately suitable (S2) while Omo and Jago series were marginally suitable (S3) for yam. Three (Omo, Ondo and Jago) soil series were marginally suitable (S3) for cassava while Irapa series was not suitable for any of the crops. Massive forest depletion and conversion of good agricultural lands to urban built-up existed in the area. The soil series identified were of varying degree of suitability in both areas for crop production. Keyword: Landuse/Landcover, Land Evaluation, Fertility capability classification, Remote Sensing.